Holistic processing of faces is intact in adults with autism spectrum disorder - Ventura, Paulo (2018)
Are face recognition difficulties in Autism Spectrum Disorders (ASD) related to impaired holistic processing? Gauthier et al. [Gauthier, I., Klaiman, C., & Schultz, R. T. (2009). Face composite effects reveal abnormal face processing in Autism spectrum disorders. Vision Research, 49, 470–478. doi:10.1016/j.visres.2008.12.007] used the face composite task in adolescents with autism and found a congruency effect that was not modulated by alignment, a result which was interpreted as reflecting qualitatively different face processing mechanisms. In the present study we tested adults with ASD in a composite face task where presentation times were manipulated and further explored whether these participants were sensitive to holistic information in faces using a new version of the composite task: VHFPT 2.0 (The Vanderbilt Holistic Face Processing Test 2.0). Results suggest that adults with ASD process faces holistically and that their facial identity processing abilities are qualitatively similar and as efficient as that of typical adults. The difference between the results of Gauthier et al. (2009) with adolescents and the results with adults here reported are interpreted in terms of a developmental delay.